2021
DOI: 10.1001/jamaoncol.2020.5935
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Molecular Testing Techniques for Diagnosis of Indeterminate Thyroid Nodules

Abstract: IMPORTANCE Approximately 20% of thyroid nodules display indeterminate cytology. Molecular testing can refine the risk of malignancy and reduce the need for diagnostic hemithyroidectomy.OBJECTIVE To compare the diagnostic performance between an RNA test (Afirma genomic sequencing classifier) and DNA-RNA test (ThyroSeq v3 multigene genomic classifier). DESIGN, SETTING, AND PARTICIPANTSThis parallel randomized clinical trial of monthly block randomization included patients in the UCLA Health system who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 37 publications
3
95
0
2
Order By: Relevance
“…Thanks to the advent of multitarget platforms (e.g., the nCounter nanoString platform), the most recent scientific approaches have been investigating gene panels able to identify peculiar expression patterns, rather than single markers [ 51 ]. This analysis strategy, in conjunction with mutation analysis, is applied to the differential diagnosis of indeterminate thyroid nodules by diagnostic commercial tests such as the Afirma Genomic Sequencing Classifier and the Thyroseq v3 Genomic Classifier [ 52 ].…”
Section: Copy Number Alterations Gene Expression and Microrna In mentioning
confidence: 99%
“…Thanks to the advent of multitarget platforms (e.g., the nCounter nanoString platform), the most recent scientific approaches have been investigating gene panels able to identify peculiar expression patterns, rather than single markers [ 51 ]. This analysis strategy, in conjunction with mutation analysis, is applied to the differential diagnosis of indeterminate thyroid nodules by diagnostic commercial tests such as the Afirma Genomic Sequencing Classifier and the Thyroseq v3 Genomic Classifier [ 52 ].…”
Section: Copy Number Alterations Gene Expression and Microrna In mentioning
confidence: 99%
“…As reported by Livhits et al, in a series of 397 indeterminate lesions, the performance of both the RNA test and DNA-RNA test increased specificity and reduced by 49% the number of nodules to avoid diagnostic surgery [124]. Furthermore, neither the RNA test nor DNA-RNA test has statistically significant difference in performance, in sensitivity (100% vs. 97%, respectively), and specificity (80% vs. 85%, respectively) [124].…”
Section: Discussionmentioning
confidence: 84%
“…Different papers showed that several mutation analysis panels are both diagnostic tests and prognostic markers. As previously described, the different molecular testing, including the Afirma GSC, ThyroSeq, and ThyGenX/ThyroMIR are characterized by different advantages and limitations so that they might contribute to a more precise and tailored management [121][122][123][124]. Nevertheless, it is relevant to assess that molecular testing still represents only an adjunct to be discussed together with valuable clinical information (e.g., nodule ultrasound size and high-risk ultra-sonographic characteristics) and cytomorphology.…”
Section: Discussionmentioning
confidence: 99%
“…Recent molecular testing (gene panel tests) have been proposed to reduce the need for diagnostic lobectomy in patients with nodules with indeterminate cytology. Livhits et al [ 17 ] investigated the effectiveness of molecular testing techniques, and in particular sought to determine whether an RNA test (Afirma genomic sequencing classifier) or a DNA-RNA test (ThyroSeq v3 multigene genomic classifier) offered superior performance in estimating the risk of malignancy of thyroid nodules with indeterminate cytology. In their randomized clinical trial of 346 patients with 372 indeterminate thyroid nodules, the prevalence of malignancy was 20%.…”
Section: Diagnosis Of Thyroid Nodules and Cancermentioning
confidence: 99%